A Steep Gall in International Environmental Law Enforcement (An Analysis of International Deforestation) - Nadir, Nadir; Gunawan, Adi (SASI, 2022)
Introduction: "Anforce the law, or the world will be destroyed" is an appropriate expression for environmental law enforcement. Many treaties have regulated the environment, mainly deforestation, and many countries have ratified these treaties. However, implementing these regulations did not necessarily stop countries from deforesting.Purposes of the Research: Furthermore, in this research, steps that could be implemented to tackle deforestation internationally were given.Methods of the Research: This research was normative juridical research that examined an international law regulation, using qualitative analysis, and using secondary data.Results of the Research: Based on international data, many countries still carried out desertification, which amounts to thousands of hectares per year. One of the reasons for the weak implementation of treaties relating to environmental protection was the absence of coercive power from international conventions over the State's sovereign authority in forest management.Weak international environmental enforcement is caused by inadequate supervision and control as well as strong authority based on state sovereignty over forest management and utilization which depends on government policies, and the system of settlement and imposition of fines that still originate from a lawsuit